Association between migration paths and mental health of new-generation migrants in China: The mediating effect of social integration - Zhou, Fenfen; Peng, Boli; Chu, Muyang; Zhang, Hui; Shi, Lishuo; Ling, Li (Frontiers in Psychiatry, 2022)
Background: The new-generation migrants born in 1980 and later are large and vulnerable internal migrants in China. Migration paths and social integration are important factors to explain for their mental health. However, they faced difficulties in social integration varying from migration paths. We aimed to explore the mediating role of social integration between migration paths and the mental health of new-generation migrants. Methods: The migration paths included urban-to-urban, urban-to-rural, rural-to-urban and rural-to-rural. Mental health was assessed by the Kessler Screening Scale for Psychological Distress (K6) and the Perceived Stress Scales (PSS-4). Social integration was measured by economic integration, life integration, maintenance of the local culture, acceptance of the host culture and psychological integration. Multiple linear regressions with bootstrapping were used to examine the mediating effect. Results: A total of 9,830 new-generation migrants were included in this study. The mean age was 26.92 (SD = 4.47) years and the proportion of rural-to-urban migrants was 63.7%. Compared with the new generation of rural-to-rural migrants, rural-to-urban migrants had higher psychological distress (β = 0.305, 95% CI: 0.152-0.458) and perceived stress (β = 0.328, 95% CI: 0.199-0.456). The bootstrapping test found that two dimensions (“life integration” and “acceptance of the host culture”) of social integration as a mediator weakened the negative effect of the rural-to-urban migration path on the mental health of new-generation migrants. Conclusion: Rural-to-urban migrants had poorer mental health, and the association was mediated by their poorer social integration. The migration policies developed to enhance social integration could effectively improve the mental health of new-generation migrants.